Memory T Cells in Pregnancy - Kieffer, Tom E. C.; Laskewitz, Anne; Scherjon, Sicco A.; Faas, Marijke M.; Prins, Jelmer R. (Frontiers in Immunology, 2019)
Adaptations of the maternal immune response are necessary for pregnancy success. Insufficient immune adaption is associated with pregnancy pathologies such as infertility, recurrent miscarriage, fetal growth restriction, spontaneous preterm birth, and preeclampsia. The maternal immune system is continuously exposed to paternal-fetal antigens; through semen exposure from before pregnancy, through fetal cell exposure in pregnancy, and through microchimerism after pregnancy. This results in the generation of paternal-fetal antigen specific memory T cells. Memory T cells have the ability to remember previously encountered antigens to elicit a quicker, more substantial and focused immune response upon antigen reencounter. Such fetal antigen specific memory T cells could be unfavorable in pregnancy as they could potentially drive fetal rejection. However, knowledge on memory T cells in pregnancy have shown that these cells might play a favorable role in fetal-maternal tolerance rather than rejection of the fetus. In recent years, various aspects of immunologic memory in pregnancy have been elucidated and the relevance and working mechanisms of paternal-fetal antigen specific memory T cells in pregnancy have been evaluated. The data indicate that a delicate balance of memory T cells seems necessary for reproductive success and that immunologic memory in reproduction might not be harmful for pregnancy. This review provides an overview of the different memory T cell subtypes and their function in the physiology and in complications of pregnancy. Current findings in the field and possible therapeutic targets are discussed. The findings of our review raise new research questions for further studies regarding the role of memory T cells in immune-associated pregnancy complications. These studies are needed for the identification of possible targets related to memory mechanisms for studies on preventive therapies.